Three‐dimensional reconstruction of deferent ducts papillae in urogenital duct system of the male rat. Issue 6 (13th January 2015) - Wakui, Shin; Motohashi, Masaya; Inomata, Tomo; Ichihara, Nobutsume; Mutou, Tomoko; Takahashi, Hiroyuki; Ikegami, Masahiro; Asari, Masao
Abstract : BACKGROUND: The rodent ejaculatory ducts penetrate the male accessory sex gland complex and open into the urethra, anatomically similar to humans. Although the deferent ducts papillae in rodents have been described at the distal end of deferent ducts, they are absent in humans, and their detailed morphology has been unclear. METHODS: The detailed anatomical structures of the distal end of the deferent ducts of rats were investigated by the computer assisted three‐dimensional reconstruction analysis using serial sections of the male accessory sex gland complexes in rats. RESULTS: The present study revealed that a pair of deferent ducts enters the ventral side of the male accessory sex gland complex, runs caudally parallel to the urethra, and then exits at about midsection of the dorso‐lateral lobe of prostate. They are composed of mammilliform papillae, called the deferent duct papillae, which dorso‐laterally protrude into the duct lumen from intra‐ventral portion of the main duct of ampullary gland. The internal surface of the deferent ducts papillae is composed of ciliated columnar epithelium continuous from the deferent ducts, while their external surface is composed of the columnar secretory epithelium of the ampullary glands. Sphincter muscles were not observed in the deferent ducts papillae, while their lamina propria were occupied by many arterial or venous capillaries. CONCLUSIONS: The deferent ducts of rat terminated at the deferent ducts papillae that located at the main duct of ampullary glands that drained into the urethra. The deferent ducts papillae might be controlled by the expansion/contraction of well‐developed papillary mucosal capillary vessels. Prostate 75: 646–652, 2015 . © 2015 Wiley Periodicals, Inc.